Beyond the naturalization and technologization of human life - Conill Sancho, Jesús (Razón y fe, 2019)
It is necessary to change the way of accessing the reality of human phenomena, which have both natural and historical character, and to revise the philosophical conceptuation with which, relying of course on the sciences, personal reality is conceptualized and configured. The historical begins with the natural, but the survival of the natural unfolds historically. There is no “fixed consistency” as suggested by the notion of being, characterized by identity and invariability, but reality is becoming through its corresponding dynamisms and, in the case of human reality, in “progress towards itself”.